ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI SKEPTISISME PROFESIONAL AUDITOR - H, Novayanti Anggraini; Y, Rahmawati Hanny (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2016)
The purpose of this study was to determine the extent to which the factors of competence, objectivity, integrity, experience, independence, and the risk of an effect on the auditor's professional skepticism. This type of research in this study is a qualitative research. The population in this study is the auditors who work in public accounting firm in the whole area of Central Jakarta. The sampling technique in this study were selected through purposive sampling technique. The number of samples in this study is 24 KAP with 150 respondents. Analysis of data using regression analysis. The result of this research is the competence of auditors have an influence on the auditor's professional skepticism . Objectivity auditor has an influence on the auditor's professional skepticism. Integrity auditor has an influence on the auditor's professional skepticism. Experience auditor has an influence on the auditor's professional skepticism. Auditor independence have an influence on the auditor's professional skepticism. Risk auditor has an influence on the auditor's professional skepticism. And competence audior , auditor objectivity, integrity auditor , auditor experience , auditor independence and auditor risk together have an influence on the auditor's professional skepticism .